No, auntie, that's false': Challenges and resources of female baby boomers dealing with fake news on Facebook - Vargas Bianchi, Lizardo (2023)
The spread of fake news on social media networks is on the rise, prompting a special interest in identification and coping skills among news consumers so that they can filter out misleading information. Studies suggest seniors share more fake news on social media; despite this, there is little literature analysing how they behave when faced with fake news. This study examines how baby boomer women handle fake news on Facebook, and the role of family members in contributing to their digital literacy in dealing with this phenomenon. A qualitative thematic analysis study was conducted using information obtained from interviews; the findings revealed that participants recognised that they could identify fake news, but were not always able to do so because of a lack of supplemental information about the news’ context or doubt about its source. Interviewees also revealed that they turned to trusted family members to assist them in developing fake news identification and filtering skills.